Die another day: Fate of heat-treated Geobacillus stearothermophilus ATCC 12980 spores during storage under growth-preventing conditions. (June 2016) - Mtimet, Narjes; Trunet, Clément; Mathot, Anne-Gabrielle; Venaille, Laurent; Leguérinel, Ivan; Coroller, Louis; Couvert, Olivier
Abstract: Geobacillus stearothermophilus spores are recognized as one of the most wet-heat resistant among aerobic spore-forming bacteria and are responsible for 35% of canned food spoilage after incubation at 55 °C. The purpose of this study was to investigate and model the fate of heat-treated survivor spores of G. stearothermophilus ATCC 12980 in growth-preventing environment. G. stearothermophilus spores were heat-treated at four different conditions to reach one or two decimal reductions. Heat-treated spores were stored in nutrient broth at different temperatures and pH under growth-preventing conditions. Spore survival during storage was evaluated by count plating over a period of months. Results reveal that G. stearothermophilus spores surviving heat treatment lose their viability during storage under growth-preventing conditions. Two different subpopulations were observed during non-thermal inactivation. They differed according to the level of their resistance to storage stress, and the proportion of each subpopulation can be modulated by heat treatment conditions. Finally, tolerance to storage stress under growth-preventing conditions increases at refrigerated temperature and neutral pH regardless of heat treatment conditions. Such results suggest that spore inactivation due to heat treatment could be completed by storage under growth-preventing conditions. Highlights: Heat-treated spores lose their viability under growth-preventing conditions. Two subpopulations were observed during non-thermal inactivation. Resistance to storage stress is modulated by heat treatment conditions. Resistance to storage stress increases at refrigerated temperature and neutral pH.